A VERY INFREQUENT ASSOCIATION OF WILLIAM-BEURAN SYNDROME AND TETRALOGY OF FALLOT - S Kollur, Banashankari; Mulimani, M S; Giraddi, Timmanna; J V, Bomman; Gowda, Shashank; Patil, Anupama; Managuli, Sushmita (International Journal of Clinical and Biomedical Research, 2017)
WB-S Autosomal Dominant Disorder is the most common genetic disorder. We report a case of 20 year old with infrequent association of WBS and TOF. Clinical examination and ECHO confirmed TOF, WB-S was suspected based on the clinical signs used in the scoring system of WB-S which were described by AAP(2001), FISH study was performed in this patient because of having more than 3 clinical signs of WB-S and FISH study showed 7q11.23 deletion and remains the gold standard laboratory investigation for WB-S. KEYWORDS: Tetralogy of Fallot; William Beuren Syndrome; Clinical Diagnosis; Fluroscence In Situ Hybridisation.